2019
DOI: 10.1186/s13643-018-0931-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between socioeconomic status and pandemic influenza: protocol for a systematic review and meta-analysis

Abstract: BackgroundPandemic mortality rates in 1918 and in 2009 were highest among those with the lowest socioeconomic status (SES). Despite this, low SES groups are not included in the list of groups prioritized for pandemic vaccination, and the ambition to reduce social inequality in health does not feature in international and national pandemic preparedness plans. We describe plans for a systematic review and meta-analysis of the association between SES and pandemic outcomes during the last five pandemics.MethodThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 23 publications
1
34
1
Order By: Relevance
“…This highlights the need for consistent approaches across jurisdictions to collect this information systematically and completely. As with influenza mortality rates, differences in socioeconomic factors might have contributed to elevated COVID-19 mortality ( 5 ). Financial or transportation-related barriers to health care access might have prevented patients from receiving timely medical care at the time of initial evaluation, resulting in more severe illness that was less amenable to treatment ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for consistent approaches across jurisdictions to collect this information systematically and completely. As with influenza mortality rates, differences in socioeconomic factors might have contributed to elevated COVID-19 mortality ( 5 ). Financial or transportation-related barriers to health care access might have prevented patients from receiving timely medical care at the time of initial evaluation, resulting in more severe illness that was less amenable to treatment ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Brisbane, Australia ecological factors appear to have played an important role in H1N1 transmission cycles (Hu et al, 2012), with temperature and precipitation being substantial variables in the evolution of the virus. There are some other works of socioeconomic studies and viruses such as (Mamelund et al, 2019), where a study is carried out between the socioeconomic levels and the influenza-related pandemics of 1918 and 2009. The foregoing demonstrates the importance of correlating the factors that can substantially alter the socio-ecological systems in which we live and to be able to study their evolution and impact on society.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that outcomes of pandemic influenza are associated with socioeconomic status. 1 Results of the meta-regression were summarized in Table 1.…”
Section: Large Citiesmentioning
confidence: 99%